Anxiety level among parents of children with Chronic Kidney Disease Undergoing Hemodialysis Therapy - أحمد آنا (Latakia University Journal -Medical Sciences Series, 2022)
Parents of children with a chronic kidney disease (CKD) have a crucial role in the management of their child’s disease. The burden on parents is high, they are often exhausted, and experience high levels of anxiety and a low quality of life, which could have a negative impact on health of their children. This study aimed to measure level of anxiety. A sample consisting of 20 parents of children with chronic kidney disease undergoing hemodialysis therapy at hemodialysis unit following to Eben Al- Rushed Hospital in Aleppo city. Data was collected by using the Arabic Version of Perceived Stress Scale 10-Items (pss10) to measure perceived level of anxiety in participants during the period from August 2020 to March 2021. Results of the current study showed that most of parents (60%) reported high level of anxiety and (40%) had an average anxiety level. A statistically significant difference was found in parental anxiety related to place of living, and number of children in family. This study recommended that renal nurses should have the ability to provide a supportive environment for parents, in order to reduce their level of anxiety, in addition to conducting more researches on a larger number of parents to identify stressors perceived by parents of children undergoing hemodialysis and causing factors.